Identification of fishing grounds and fishing gear distribution as basis for fisheries management in North Aceh Waters - Imamshadiqin Imamshadiqin; Salmarika Salmarika; Muliari Muliari; Randa Fadhilah Tambunan; Zulhaikal Hikmal; Alvi Rahmah; Imelda Agustina; Ratna Mutia Aprilla (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
Determining the fishing ground is a factor that greatly determines the success of fishing operations. In determining fishing grounds, fishermen generally still use traditional methods. One of the more advanced ways of determining fishing grounds is by using remote sensing through oceanographic distribution. This study aims to determine the distribution of fishing grounds and fishing gear based in North Aceh Waters. The method used in this study is direct observation in the waters. Observations were made on fishing boats at each station to obtain data on the coordinates of fishing areas and fishing gear. The sampled vessels totaled 40 vessels (each station had eight vessel samples). Mapping analysis was conducted by using Map Source and Arc Map applications. The fishing grounds of small-scale fishers in North Aceh Waters are between 2 - 44 nautical miles. The Coordinate point distribution of fishing areas Krueng Mane is at 5°37'51.30“LU; 96°54'26.26” BT, Bungkah is at 5°16'19.91” LU; 96°58'9. 32“BT, Bangka is at 5°15'34.70” LU and 97°1'58.48“BT, Kuala Keuruto Barat is at 5°10'21.22” LU and 97°15'32.59” BT, and Kuala Cangkoi is at 5°11'26.04” LU and 97°18'38.15” BT. The dominant fishing gear used by fishermen is handlines, followed by purse seine and Katrol or Langge. Fishing aids are FADs and bait.